Effect of a Clinical Decision Support Tool for Identifying Patients Benefiting from End-of-Life Discussions on Emergency Department Clinician Behavior - Dilip, Monisha; Rothenberg, Craig; Van Tonder, Reinier; Jubanyik, Karen; Venkatesh, Arjun K.; Rhodes, Deborah; Sangal, Rohit B.; Kim, Nancy (Applied Clinical Informatics, 2025)
Electronic health records (EHRs) are intended to improve clinical practice, but excessive alerts can be counterproductive, leading to workarounds. The Mortality Surprise Question (MSQ), a tool for identifying patients who might benefit from early end-of-life discussions, was integrated into the Emergency Department (ED) EHR admission process.This study investigated how the staged implementation of a clinical decision support tool at the point of admission order entry affected ED clinician admission order practices.This retrospective cohort study examined ED admission orders from 2023 across three EDs. Clinicians used either the Quicklist or Disposition tab in the Epic EHR for admissions. The MSQ was introduced in two phases, first to the Quicklist on May 31, 2023, and then to the Disposition tab on September 11, 2023. Admissions from both tabs were analyzed pre- and post-MSQ implementation. Statistical analysis included chi-square testing to compare the admission source in the EHR after each phase of implementation of the MSQ to examine changes in the clinicians' admission workflow, with further categorization based on clinician EHR experience.Overall, 53,897 patients were admitted from the ED, with 29,542 (55%) admissions via the Quicklist and 24,355 (45%) via the Disposition tab. A statistically significant difference was found in Quicklist admission proportions before and after MSQ implementation in both workflows. As compared with clinicians with less than 2 years of experience with the EHR, clinicians with 2 to 4 years of EHR use were less likely to use the Quicklist after MSQ implementation, whereas those with over 4 years of use were more likely to use it.The MSQ disrupted established workflows, prompting clinicians to initially adopt more effortful alternatives to avoid the new cognitive task. Embedding the MSQ into these alternatives reduced resistance, highlighting that removing optionality promotes adoption. Accounting for clinician habits and potential workarounds can enhance the integration and efficiency of new quality improvement measures.
Keywords: workaround; EHR; health record; workflow; Mortality Surprise Question